History and the social web : a collection of essays - Krey, August C. (August Charles), 1887-1961 (University of Minnesota Press, 1955)
History and the Social Web was first published in 1955. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. In this volume of twelve essays a distinguished historian demonstrates that the roots and branches of history form a continuous social web, that the events and societies of pasts eras and modern times form a complex and interlocking pattern when seen as a whole, and that a knowledge of history has a profound application to the problems and pleasures of the present. The volume includes the well-known essay, "A City That Art Built," which has long been out of print. The first group of essays is devoted to aspects of medieval and renaissance history, and those in the second section point up the continuity of the thread of world history. The essays on law, education, and medicine which form a part of the first section will be of particular interest to members of these professions